The winged helix domain of MORF binds CpG islands and the TAZ2 domain of p300 - Dustin C. Becht; Akinori Kanai; Soumi Biswas; Mohamed Halawa; Lei Zeng; Khan L. Cox; Michael G. Poirier; Ming-Ming Zhou; Xiaobing Shi; Akihiko Yokoyama; Tatiana G. Kutateladze (iScience, 2024)
Summary: Acetylation of histones by lysine acetyltransferases (KATs) provides a fundamental mechanism by which chromatin structure and transcriptional programs are regulated. Here, we describe a dual binding activity of the first winged helix domain of human MORF KAT (MORFWH1) that recognizes the TAZ2 domain of p300 KAT (p300TAZ2) and CpG rich DNA sequences. Structural and biochemical studies identified distinct DNA and p300TAZ2 binding sites, allowing MORFWH1 to independently engage either ligand. Genomic data show that MORF/MOZWH1 colocalizes with H3K18ac, a product of enzymatic activity of p300, on CpG rich promoters of target genes. Our findings suggest a functional cooperation of MORF and p300 KATs in transcriptional regulation.